MITIGATION PRACTICES FOR GREENHOUSE GAS EMISSIONS IN ANIMAL HUSBANDRY - MARAM HARANI, (The Journal of Research ANGRAU, 2026)
Animal husbandry significantly contributes to greenhouse gas (GHG) emissions, withlivestock accounting for an estimated 7 to 18 percent of global anthropogenic emissions. Mitigationstrategies targeting enteric methane (CH4) and management of manure are critical for loweringthe environmental effect of animal production. This paper reviews current mitigation practices,including dietary strategies, feed supplements, manure management techniques, and climatesmart livestock management. Emphasizing the complex interactions between these practices,this review highlights the contribution of improving Animal performance and well-being as keystrategies for GHG emission reduction. It also explores the capability for synergistic approachesto limit the emissions across multiple components of the animal production system